Different absorption and metabolism of ginsenosides after the administration of total ginsenosides and decoction of Panax ginseng. (22nd May 2020) - Liu, Jihua; Li, Ting; Wang, Jia; Zhao, Chunfang; Geng, Cong; Meng, Qin; Du, Guangguang; Yin, Jianyuan
Abstract : Rationale: Panax ginseng C.A. Meyer (PG), which contains polysaccharides and ginsenosides as the major bioactive components, has been used to promote health and treat diseases for thousands of years in China. Total ginsenosides were extracted from a decoction of Panax ginseng (GD), which included both ginsenosides and polysaccharides, and dissolved in water to obtain a total ginsenosides aqueous solution (TGAS). To study their absorption and metabolism, the pharmacokinetics (PK) and metabolites of ginsenosides in vivo were investigated after the administration of GD and TGAS. Methods: Rat and mice plasma samples were collected after the administration of GD and TGAS. Ultra‐performance liquid chromatography coupled with time‐of‐flight mass spectrometry was used with the UNIFI platform to identify metabolites in the plasma sample. The pharmacokinetic parameters were calculated using a noncompartmental method in the Drug and Statistics software package. Results: Thirty ginsenoside metabolites were identified in mice plasma, of which only seven were found in the rat plasma after the administration of GD. The PK of ginsenosides Rb1, Rc, and Rd were also determined after the oral administration of GD and TGAS and showed significant differences in the pharmacokinetic parameters. Conclusions: There was no difference in the biotransformation pathways after the oral administration of GD and TGAS, indicating that there was no influence of polysaccharides on the biotransformation of ginsenosides in vivo . However, the pharmacokinetic parameters were different after the administration of GD and TGAS, possibly because of the polysaccharides in GD. This study should be of significance in exploring the basis of PG bioactivities and lays the foundation for the further development of new drugs using PG.